'We can't go on like this'. (2nd March 2020) - Leitch, Neil
Abstract : As the Comprehensive Spending Review and the end of the funding freeze loom, 2020 offers new opportunities to ramp up the fight for fair early years funding. What comes after that is 'up to us' says Neil Leitch.